2017
DOI: 10.1080/10903127.2017.1358782
|View full text |Cite
|
Sign up to set email alerts
|

Sternal Route More Effective than Tibial Route for Intraosseous Amiodarone Administration in a Swine Model of Ventricular Fibrillation

Abstract: The SIO and IV routes of amiodarone administration were comparable. The TIO group took nearly three times longer to reach Tmax than the SIO and IV groups, likely indicating depot of lipid-soluble amiodarone in adipose-rich tibial yellow bone marrow. The SIO route was more effective than the TIO route for amiodarone delivery in a swine model of VF with ongoing CPR. Further investigations are necessary to determine if the kinetic differences found between the SIO and TIO routes in this study affect survival of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“… 34 Burger et al found that for amiodarone, a lipid soluble medication, C(max) was slowest for tibial IO and equivalent for both sternal IO and PIV. 35 The authors hypothesized that the lipid-rich marrow in the tibial site resulted in an amiodarone depot, delaying release to the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 34 Burger et al found that for amiodarone, a lipid soluble medication, C(max) was slowest for tibial IO and equivalent for both sternal IO and PIV. 35 The authors hypothesized that the lipid-rich marrow in the tibial site resulted in an amiodarone depot, delaying release to the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Additionally, the insertion site has minimal overlaying tissue except for in extreme obesity, again making identification straightforward. 35 Sternal IO devices also have more direct access to central circulation via the venous drainage of the manubrium, as Burgert et al noted, and may actually benefit from “the hydraulic action of chest compressions” in cases of cardiac arrest. 33 , 35 Finally, FAST1 IO devices do not require selection of different needle sizes and rely on deployment of a single needle size to the correct depth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An amiodarone 300 mg bolus diluted in 10 mL of 5% glucose solution was administered after cardiac arrest induction. According to previously published data about monitoring amiodarone PK during CPR in swine models [ 18 , 19 , 20 ], serial blood specimens (10 mL) were collected from the aortic arterial line, at 30, 60, 90, 120, 150, 180, 240, 300 s, and at 6, 8, 10, and 12 min after amiodarone injection. Prior to each specimen collection, 10 mL of blood were aspirated and discarded to avoid any dilution effect or contamination.…”
Section: Methodsmentioning
confidence: 99%